STUDIES ON FLUTTER AND FIBRILLATION 2 THE INFLUENCE OF ARTIFICIAL OBSTACLES ON EXPERIMENTAL AURICULAR FLUTTER - ROSENBLUETH, ARTURO; RAMOS, JG (INSTITUTO NACIONAL DE CARDIOLOGIA, DEPARTAMENTO DE FISIOLOGIA, CD. MEXICO, DF, MEX, 1947)
In denervated normal dog's auricles, enduring activity with the characteristics of flutter, as defined by the circus-movement theory, can be elicited only rarely by electrical stimuli. If the conduction of impulses through the auricular fibers which lie b
AM HEART J
Keywords: STUDIES, FLUTTER, FIBRILLATION, INFLUENCE, ARTIFICIAL, OBSTACLES , EXPERIMENTAL, AURICULAR, FLUTTER; CIENCIAS MEDICAS; MEDICINA INTERNA; CARDIOLOGIA